Usability and User Experience of Cognitive Intervention Technologies for Elderly People With MCI or Dementia: A Systematic Review - Contreras-Somoza, Leslie María; Irazoki, Eider; Toribio-Guzmán, José Miguel; de la Torre-Díez, Isabel; Diaz-Baquero, Angie Alejandra; Parra-Vidales, Esther; Perea-Bartolomé, María Victoria; Franco-Martín, Manuel Ángel (Frontiers in Psychology, 2021)
Introduction: Incorporating technology in cognitive interventions represents innovation and making them more accessible, flexible and cost-effective. This will not be feasible without an adequate fit between user and technology. Given the importance of developing cognitive interventions whose technology is according to elderly with cognitive impairment, the objective of this systematic review is found evidence about usability and user experience (UX) measures and features of stimulation, training and cognitive rehabilitation technologies for older adults with mild cognitive impairment (MCI) or dementia. Method: Medline, PubMed, Scopus, ScienceDirect and PsycINFO databases were used for literature searches from the last ten years (2009-2019) and three researchers independently reviewed potential studies for eligibility, following specific inclusion criteria. A systematic review of the studies was conducted, presenting a qualitative synthesis of usability and UX measures with their outcomes, study characteristics and cognitive intervention technologies features. Results: Ten studies were selected: 5 were cognitive stimulation, while the other 5 were cognitive training; 60% of them were programs with a serious game format that mainly used the computer. Efficiency and effectiveness were the most frequent measures for collecting objective data of usability, which showed that elderly with cognitive impairment were able to complete tasks (60%), required more time (45%) and help (40%). Regarding the subjective usability data, questionnaires and scales were the most used in UX. In 9 studies subjects with cognitive impairment reported a positive experience, despite perceived difficulties with the interface in 5 studies. Conclusion: Measuring the usability and UX of cognitive intervention technologies for older adults with MCI or dementia allows an integrated view of their needs, characteristics and preferences for the proper development of these technologies. More research is needed to integrate these populations into usability and UX studies, as well as standardized tools and a consensus on the relationship of these terms to guarantee the future effectiveness of cognitive intervention technologies.